Decoration of cyclodextrin on surface of porous nano silica via disulfide bond for the controlled drug release - Nguyen, Dai Hai; Thi, Thai Thanh Hoang (Vietnam Journal of Science and Technology, 2020)
Porous nano-silica (PNS) as promising targeted drug nanocarriers has become a new area of interest in recent years due to their tunable pore sizes and large pore volumes, high chemical and thermal stability, and excellent biocompatibility. These unique structures of PNS facilitate effective protecting drugs from degradation and denaturation. However, it has certain limitations for being used in pharmaceutical such as a burst release of encapsulated drugs. In this study, the effects of grafting cyclodextrin (CD) as gatekeeper through the biodegradable disulfide bonds on doxorubicin (DOX) release was investigated. The morphology and pore channel structures of these modified PNS were assessed by transmission electron microscopy (TEM). Fourier transform infrared spectroscopy (FT-IR) was utilized to evaluate the functional groups on PNS surface. In vitro tests were conducted for the drug loading and releasing efficiency. The results demonstrated that the prepared DOX@PNS-SS-A/CD was spherical shape with an average diameter of 45 nm, drug loading efficiency of 60.52 ± 2.12%, and sustained release. More importantly, MTT assay showed that PNS-SS-A/CD was biocompatible nanocarriers. In addition, the modified PNS incorporating DOX could significantly eliminate the toxicity of free DOX. As a result, the development of PNS-SS-A/CD may offer a promising candidate for loading and sustained release of DOX in cancer therapy.